2014
DOI: 10.1002/nag.2241
|View full text |Cite
|
Sign up to set email alerts
|

A distinct element method numerical investigation of compaction processes in highly porous cemented granular materials

Abstract: In this paper, the results of an oedometric numerical test campaign, performed by means of a 3D Discrete Ele- ment Code on idealised cemented granular cylindrical specimens, are illustrated. The idealised microstructure taken into account is characterised by the following: (i) rigid grains bonded to one another; (ii) a high void ratio; and (iii) two different families of voids: the micro and the macro-voids. The compaction process developing within the specimens, as well as the localization along tabular zones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…To validate both the mechanical hardening and plastic potential parameters, a series of oedometric compression test results on dry and wet Gravina calcarenite samples were employed (Figure ). As is evident, the experimentally observed post yielding plateau is not captured in a satisfactory way by the model because in this phase of the test, compaction bands develop within the specimen , while the simulations implicitly assume the sample not to localize. Nevertheless, the mechanical hardening and plastic potential parameters already calibrated in the previous section fit quite well the mechanical behavior of the calcarenite when loaded under oedometric conditions.…”
Section: Model Validationmentioning
confidence: 98%
See 1 more Smart Citation
“…To validate both the mechanical hardening and plastic potential parameters, a series of oedometric compression test results on dry and wet Gravina calcarenite samples were employed (Figure ). As is evident, the experimentally observed post yielding plateau is not captured in a satisfactory way by the model because in this phase of the test, compaction bands develop within the specimen , while the simulations implicitly assume the sample not to localize. Nevertheless, the mechanical hardening and plastic potential parameters already calibrated in the previous section fit quite well the mechanical behavior of the calcarenite when loaded under oedometric conditions.…”
Section: Model Validationmentioning
confidence: 98%
“…Sometimes, owing to the particular microstructure of the material, axial strains localize along horizontal layers. This phenomenon is known as compaction banding . As the formation of a compaction band is a dynamic process, the jumps in vertical strains and the associated discontinuities in the radial stress are justified.…”
Section: Model Validationmentioning
confidence: 99%
“…Issen and Rudnicki (2000) adapted the analysis of shear bands from Rudnicki and Rice (1975) to compaction bands and demonstrated that compaction bands occur in porous materials that are described by a yield surface with a cap. Numerical analyses with the finite element method (FEM) (Das and Buscarnera 2014;Chemenda 2009) as well as the discrete element method (DEM) (Wu et al 2020;Katsman et al 2005;Dattola et al 2014) were used to investigate the mechanism leading to the formation of compaction bands in porous rocks. The behaviour of bonded geo materials was studied via theoretical investigations (Tengattini et al 2014;Nova et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The Discrete Element Method is based on an idealization of the mesostructure using discrete particles, which interact through inter-particle forces and contact mechanisms. This discretization method allows for an explicit representation of the material microstructure with soft [34][35][36] and hard inclusions [37][38][39][40]. Thus, through an explicit representation of the pore structure and by consideration of the pore collapse mechanism, DEM is capable of simulating the essential physics of compressible lining materials.…”
Section: Introductionmentioning
confidence: 99%